‘Affording’ new approaches to couples who inject drugs: A novel fitpack design for hepatitis C prevention - Fraser, Suzanne; Treloar, C.; Gendera, S.; Rance, J. (Elsevier BV, 2017)
© 2017 Background In the West, hepatitis C is predominantly transmitted via the sharing of contaminated drug-injecting equipment. Although the majority of this sharing occurs between sexual partners, the responsibility for avoiding transmission has long been conceived as an individual responsibility, with prevention measures such as the distribution of sterile injecting equipment such as injecting packs (‘fitpacks’) aimed at individuals without regard for the social contexts of injecting. In this article we draw on the work of Bruno Latour to reconceptualise the fitpack. We argue that the fitpack is not inert or neutral in its meaning or effects, that instead it ‘affords’ particular meanings and actions, for example, that injecting is an individual practice and safety an individual responsibility. Method To challenge these affordances, we developed a new fitpack prototype aimed at couples, along with related health promotion messages. We asked 13 couples who inject drugs to examine and reflect on these new objects and messages. Results Overall, we found a high level of support for the broad idea of couples-oriented materials, as well as for our prototype and associated materials. Participants identified opportunities for improving the materials and commented on implications of the symbols and language used. Together the interviews demonstrated ways in which the new fitpacks and messages could afford couples-oriented safe injecting, and better recognition of relationships that are often dismissed by researchers and health care providers as insincere. Conclusions These findings demonstrate that first, there is a need and desire for a greater range in harm reduction resources. Second, it is essential to find ways of better acknowledging the validity and value of relationships between people who inject. Third, and more broadly, recognition must be given to the role of technological objects in materialising meanings and, as Latour might put it, ‘moralities’, and in turn to interrogating these meanings and moralities.